Wideband omnidirectional printed dipole antenna with dumbbell‐shaped open sleeve for wireless communication applications. Issue 15 (1st December 2014) - Zhang, Zhi‐Ya; Yang, Xiao‐dong; Zuo, Shao‐Li; Fu, Guang
Abstract : The wideband performance of a printed dipole antenna with dumbbell‐shaped open sleeve structure is presented. Besides using printed dipole for omndirectional radiation patterns, the dumbbell‐shaped open sleeve structure is employed to improve the impendence matching at lower band because of producing two resonant points; whereas two parasitical patches are also used to increase the bandwidth of the lower band. The four tuning stubs and the coupling feed can effectively enhance the impendence bandwidth at upper band. A wideband impedance characteristic of about 91.4% for voltage standing wave ratio (VSWR) ≤ 2 ranging from 0.89 to 2.39 GHz is obtained. The omnidirectional radiation patterns in the whole operation bands are achieved where the un‐roundness in the H ‐plane is <2.2 dB. It is sufficient for accommodating recent wireless communication services such as GSM900, DCS1800, PCS1900, UMTS, IMT2000 and Wibro.